A Review of Lean Concept and its Application to Sustainable Construction in the UK - Ogunbiyi, Oyedolapo Ekundayo; oladapo, Adebayo Akanbi; Goulding, Jack Steven (International Journal of Sustainable Construction Engineering and Technology, 2013)
The UK Government has recognised the importance of the construction industry in achieving the overall goals of sustainable development. Therefore the Government has put several policies and strategies in place to achieve a more sustainable construction. Sustainable construction is considered as the application of sustainable practices and sustainable development principles to the activities of the construction sector. Lean construction is a new production philosophy which has the potential of bringing innovative changes in the construction industry. The Lean principles focus on the minimisation of both material and process wastes which in turn contribute to sustainable construction in terms of energy consumption and improvement in health and safety etc. This study aims at exploring the concept of sustainable construction and examines how the lean approach can impact on the sustainability practices within the construction industry. The study uses literature review to achieve the stated aim. The findings revealed that the application of lean construction principle, tools and methods have direct contributions to the attainment of sustainable practices within the construction industry. However, the study postulates that the better understanding of lean concept, proper implementation and integration of lean and sustainability concepts are required for lean construction to contribute to sustainable construction.